2014
DOI: 10.4049/jimmunol.1302681
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Cell CD45 Regulates Lymphopenia-Induced T Cell Proliferation

Abstract: The leukocyte-specific tyrosine phosphatase, CD45, severely impacts T cell development and activation by modulating TCR signaling. CD45-deficient (CD45KO) mice have reduced peripheral T cell numbers where CD8 T cells are underrepresented. In this article, we show that CD45KO mice are unable to support efficient homeostatic proliferation, affecting CD8 T cells more than CD4 T cells. Using CD45-RAG1 double-deficient (45RAGKO) mice, we show that lymphopenia-induced proliferation (LIP) of CD45-sufficient T cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The enrichment of DMGs into the glycan synthesis pathway may be related to the regulation of pathogen recognition. At the same time, immune-related DMGs, such as VAV3 , PLCG2 , TEC and PTPRC participated in multiple immune pathways ( Miller and Berg, 2002 ; Tybulewicz, 2005 ; Saunders et al, 2014 ; Magno et al, 2019 ). Most of these genes act on adaptive immunity and are involved in the development and activation of T cells, which may be related to the stronger cellular immunity of the wildness training pandas mentioned in transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of DMGs into the glycan synthesis pathway may be related to the regulation of pathogen recognition. At the same time, immune-related DMGs, such as VAV3 , PLCG2 , TEC and PTPRC participated in multiple immune pathways ( Miller and Berg, 2002 ; Tybulewicz, 2005 ; Saunders et al, 2014 ; Magno et al, 2019 ). Most of these genes act on adaptive immunity and are involved in the development and activation of T cells, which may be related to the stronger cellular immunity of the wildness training pandas mentioned in transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that, upon the transfer of polyclonal CD45 þ / þ T cells into naive CD45RAG À / À and RAG À / À mice, there was reduced lymphopenia-induced proliferation of the transferred T cells in CD45RAG À / À mice, resulting in lower frequency and number of CD45 þ / þ T cells in the spleen and peripheral lymph nodes on day 7 after transfer. 7 However, upon inflammation induced by DSS, there was no significant difference in T-cell frequency or number in the spleen between CD45RAG À / À and RAG À / À mice (see Supplementary Figure S7), suggesting that lymphopenia-induced proliferation is not a contributing factor to the reduction of colon T cells observed in CD45RAG À / À mice. In addition, there was no significant increase in the percentage of Foxp3 þ T cells within CD4 þ or CD8 þ T cells in the spleen, mLNs, and LP of the CD45RAG À / À mice (see Supplementary Figure S8), indicating that increased numbers of Tregs were not the reason for the reduced colitis observed in CD45RAG À / À mice.…”
Section: Cd45 Helps Promote Ra Production By Dcs In the Mlns In Dss-imentioning
confidence: 91%
“…CD45E6 À / À have significantly reduced numbers of T cells in the spleen and periphery and CD45E9 À / À mice have even less T cells compared with wild-type (WT) mice. 4,5,7 Although most leukocytes are negative for CD45, in the CD45E6 À / À mice, a small percentage of T cells express low levels of the CD45RB isoform, whereas in CD45E9 À / À mice all the leukocytes, including the T cells, are CD45 null. The CD45E6 À / À T cells express higher levels of LFA-1 and CD44, 8 and we have found increased levels of LFA-1 on CD45E9 À / À T cells (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the mechanisms of regulation of CD45 expression have been poorly studied, and there is no evidence of ligand-induced activation of CD45. It is possible that CD45 is permanently active, and that it causes dephosphorylation of Src family kinases, maintaining them in a working, non-phosphorylated state [51].…”
Section: Discussionmentioning
confidence: 99%